Flexural Performances of Square Concrete Filled CFRP-Steel Tubes (S-CF-CFRP-ST). Issue 8 (August 2015) - Wang, Qing-Li; Li, Jia; Shao, Yong-Bo; Zhao, Wei-Juan
Static behavior of sixteen square concrete filled CFRP-steel tubular (S-CF-CFRP-ST) flexural members are experimentally investigated in this paper. The test results show that the moment-curvature curves on the cross-section of the composite members at the mid-span can be divided into three stages, i.e., elastic stage, elastoplastic stage and softening stage. The longitudinal CFRP can enhance the flexural load carrying capacity and the stiffness of the members effectively. Analyses on the experimental results show that the steel tube and its outer CFRP material can cooperate in both longitudinal and transverse directions, and the distribution of the longitudinal strains of the steel tube over the cross-section depth satisfies with plane section assumption approximately. In addition, the steel tube under longitudinal tension has no transverse confinement effect on the core concrete. The failure modes and the moment-curvature curves on the cross-section of the specimens at the mid-span are simulated by using finite element method. The predicted results agree well with the experimental values. The strains of the steel material, the transverse deformation of the specimens at the mid-span, the stresses and the strains of the concrete, the interaction force between the steel tube and the concrete, and the effect of the adhesive strength on the static behavior are all analyzed. Finally, equations for calculating flexural load carrying capacity of the composite members are proposed. The presented equations are evaluated and found to be able to predict the strength accurately.